2013
DOI: 10.1016/j.ahj.2013.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Race, exercise training, and outcomes in chronic heart failure: Findings from Heart Failure - A Controlled Trial Investigating Outcomes in Exercise TraiNing (HF-ACTION)

Abstract: Background The strength of race as an independent predictor of long-term outcomes in a contemporary chronic heart failure (HF) population and its association with exercise training response have not been well established. We aimed to investigate the association between race and outcomes and to explore interactions with exercise training in patients with ambulatory HF. Methods We performed an analysis of HF-ACTION, which randomized 2331 patients with HF having an ejection fraction ≤35% to usual care with or w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 30 publications
2
17
0
1
Order By: Relevance
“…21 We found that the vast majority of Jackson Heart Study participants with QRS prolongation had a QRS duration of 100 to 119 msec (ie, 89% of prolongation cases). These findings support previous research suggesting important differences in ventricular conduction by race 10,22,23 and highlight the high prevalence of mild QRS prolongation in African Americans. Genetic differences may explain, in part, these racial differences in QRS duration.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…21 We found that the vast majority of Jackson Heart Study participants with QRS prolongation had a QRS duration of 100 to 119 msec (ie, 89% of prolongation cases). These findings support previous research suggesting important differences in ventricular conduction by race 10,22,23 and highlight the high prevalence of mild QRS prolongation in African Americans. Genetic differences may explain, in part, these racial differences in QRS duration.…”
Section: Discussionsupporting
confidence: 91%
“…3,8 Racial differences in ventricular conduction have been identified in the general population and among patients with cardiac disease. 9,10 However, associations between QRS duration and clinical outcomes in African Americans have not been well characterized. The availability of electrocardiogram information on more than 5000 African American participants in the Jackson Heart Study allows a comprehensive investigation of the relationship between QRS duration and mortality in this population.…”
mentioning
confidence: 99%
“…Lastly, it appears that the highest rates of rehospitalization in these patients occurred despite their objective measures of milder HF; this implies that therapies aimed at improving disease state alone would not decrease these patients’ rehospitalization rates. Rather, a focused effort on understanding the global reasons for rehospitalization might result in more effective preventive methods (31,32). …”
Section: Discussionmentioning
confidence: 99%
“…The primary outcomes for the present analysis were change in peak VO 2 and change in KCCQ from baseline to 3 months, as in previous HF-ACTION analyses, because of the increased missingness at later time points (15,16). The secondary outcome was change in 6MWD from baseline to 3 months.…”
Section: Methodsmentioning
confidence: 99%
“…To account for the missing data at 3 months for the outcomes of interest, inverse weighting for missingness was performed. Specifically, subjects in the regression model were weighted by the inverse of their probability of having a nonmissing response similar to recent analyses in HF-ACTION (15,16). This should reduce the bias that would have been present in a complete case analysis by assigning higher weight to observed data subjects who were similar to subjects who were more likely to have missing data (15).…”
Section: Methodsmentioning
confidence: 99%